International Monetary Fund (IMF) Dan Penanggulangan Krisis Moneter Di Indonesia - Muhammad Lutfi; Hendra Ibrahim (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Research on international economics becomes interesting considering the existence of anomalies such as different economic systems and economic crises throughout the world, especially in Asia, during the last decade. This article discusses the nature of services offered by the International Monetary Fund (IMF), a global organization with an important role in the economy. An organizational profile is prepared along with some comments on the fundamental issues facing the group's workings. Important theoretical perspectives are incorporated throughout the narrative. The IMF has come up with a number of sources that provide all the information necessary to take more effective steps to help various economies come out of their current economic crises.